Thermodilution-derived coronary absolute flow and resistance in patients with different INOCA endotypes. (3rd October 2022) - Smits, P M; Laforgia, P L; Sijbring, M; Den Ruijter, H M; Smits, P C; Paradies, V
Abstract: Background: Thermodilution-derived measurement of absolute coronary flow and resistance has been recently validated by using a dedicated microcatheter and a pressure-temperature guidewire. Coronary absolute flow (AbsF) and derived absolute resistance (AbsR) can give precious information about the microcirculation in patients with ischemia and non-obstructive coronary artery disease (INOCA). The correlation with different INOCA endotypes has been so far poorly investigated. Methods: 108 INOCA patients underwent a complete evaluation of underwent coronary function testing, including acetylcholine (ACH) provocation testing, adenosine testing (CFR/IMR) and functional assessment of the left anterior descending artery using thermodilution-derived measurement of AbsF and AbsR. Results: Among 108 INOCA patients, 64% showed coronary microvascular dysfunction (CMD) with positive ACH reaction (ACH+) and/or abnormal CFR/IMR (CFR/IMR+), of whom 38% presenting with an isolated structural component (CFR/IMR+) and 62% with an isolated vasospastic component (ACH+). Among ACH+ patients, epicardial vasospastic angina was detected in 28.2% of the patients. AbsF was found significantly lower in ACH+ patients than in ACH− patients (0.174±0.09 vs 0.2019±0.09, p=0.03). Similarly, a trend of higher AbsR values was found in ACH+ patients as compared to ACH− (612.5±226.5 vs 524.5±171.2, p=0.07, Fig. 1A). AbsF was found significantly lower in patients with coronary microvascular dysfunction (CMD) than in patients without either vasospastic or structural component of CMD (0.172±0.06 vs 0.202±0.09, p=0.05) and AbsR showed a trend towards higher values in patients with CMD than patients without CMD. (609.3±208.8 vs 557.7±193.1, p=0.08, Fig. 1B) AbsF and AbsR did not differ in patients with and without abnormal adenosine testing only: AbsF (0.176±0.06 vs 0.197±0.09, p=0.31) and AbsR 589.8±183.0 vs 565.2±190.2, p=0.27). A modest correlation was found between AbsQ and IMR (r: −0.2: p: 0.05, Fig. 2). Conclusion: Coronary vasomotor dysfunction is highly prevalent in INOCA patients and a complete coronary function evaluation, including provocative test should be performed. Continuous thermodilution is safe and easily implemented in INOCA patients and provide new insights in the assessment of INOCA endotypes with high reproducibility. The exact diagnostic and prognostic value of these measurements, and their optimal cutoff, should be assessed in future studies. Funding Acknowledgement: Type of funding sources: None.